Answer:
f(n) = -n^2 -3n +5
Step-by-step explanation:
Suppose the formula is ...
f(n) = an^2 +bn +c
Then we have ...
f(1) = 1 = a(1^2) +b(1) +c
f(2) = -5 = a(2^2) +b(2) +c
f(3) = -13 = a(3^2) +b(3) +c
__
Here's a way to solve these equations.
Subtract the first equation from the second:
-6 = 3a +b . . . . . 4th equation
Subtract the second equation from the third:
-8 = 5a +b . . . . . 5th equation
Subtract the fourth equation from the fifth:
-2 = 2a
a = -1
Then substituting into the 4th equation to find b, we have ...
-6 = 3(-1) +b
-3 = b
and ...
1 = -1 +(-3) +c . . . . . substituting "a" and "b" into the first equation
5 = c
The formula is ...
f(n) = -n^2 -3n +5
no, this is false. 1 is greater than 12/20.
Answer:
Answer:
4.8 gigabytes
Step-by-step explanation:
Let the number of gigabytes of data = x
Xavier pays a flat cost of $44 per month and $3 per gigabyte. He wants to keep his bill at $58.40 per month.
The above expression above is represented by the equation:
$44 + $3 × x = $58.40
44 + 3x = 58.40
Solving for x
Subtract 44 from both sides
44 - 44 + 3x = 58.40 - 44
3x = 14.4
x = 14.4/3
x = 4.8 gigabytes
Step-by-step explanation:
Answer:
3/6 or 1/2.........................
Answer:
T
Step-by-step explanation:
Just did it